2011
DOI: 10.1055/s-0031-1271776
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens Modulate RANKL-RANK/Osteoprotegerin Mediated Interleukin-6 Effect on Thyrotoxicosis-related Bone Turnover in Mice

Abstract: Interleukin-6 has been shown to cause imbalance between bone resorption and formation in thyrotoxicosis. The aim of the present study was an attempt to estimate the influence of estrogens on thyrotoxicosis-related disturbances in bone turnover in relation to RANKL-RANK/osteoprotegerin system in IL-6 deficient mice. The study was performed on 56, 12-13 weeks old, female mice: C57BL/6J (wild-type; WT) and C57BL/6J (IL6-/-Kopf) (IL-6 knock-out; IL6KO). The mice were randomly divided into 8 groups with 7 mice in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…until 24 weeks of age, when mice were killed (Spencer and West, 1961;Weinstein et al, 1991;Weinstein et al, 1994;Wistuba et al, 2007;Dong et al, 2010;Mysliwiec et al, 2011;Buras et al, 2014). Analysis of serum samples indicated that T4 concentration was increased in T4-treated mice (Supporting Information Figure S1A).…”
Section: T4 Supplementation Enhances Glucose Clearance In Healthy C57mentioning
confidence: 99%
“…until 24 weeks of age, when mice were killed (Spencer and West, 1961;Weinstein et al, 1991;Weinstein et al, 1994;Wistuba et al, 2007;Dong et al, 2010;Mysliwiec et al, 2011;Buras et al, 2014). Analysis of serum samples indicated that T4 concentration was increased in T4-treated mice (Supporting Information Figure S1A).…”
Section: T4 Supplementation Enhances Glucose Clearance In Healthy C57mentioning
confidence: 99%
“…11 Studies suggest that estrogen can modulate the RANKL-OPG system and increase levels of OPG, causing a decrease in the RANKL/OPG protein ratio. 12,13 Under certain circumstances, disequilibrium in the RANK/RANKL/OPG triad induces an enhanced activity of osteoclasts assessed by an increase in tartrate-resistant acid-phosphatase (TRAP) staining. 14,15 Because multinuclear TRAP-positive cells resorb bone, TRAP is a specific osteoclast differentiation marker.…”
mentioning
confidence: 99%
“…These include a relative deficiency of insulin-like growth factor type I, dehydroepiandrosterone sulfate [287], vitamin D receptor (VDR) polymorphisms [288] and estrogen [289]. The question as to whether prolonged hyperthyroidism due to L-T4 treatment increases the risk of fractures also remains controversial.…”
Section: Discussionmentioning
confidence: 99%